Queering kinship, overcoming heteronorms - Lasio, D. (2020)
Although same-sex couples and their offspring have been legitimised in many European countries, heteronormativity is still embedded in institutions and practices, thereby continuing to affect the daily lives of LGBT individuals. Italy represents a clear example of the hegemonic power of heteronormativity because of the fierce opposition to recognising lesbian and gay parenthood among many parts of society. This paper focuses on the peculiarities of the Italian scenario with the aim of highlighting how heteronormativity works in contemporary neoliberal contexts. By drawing on queer and feminist perspectives, the article also analyses how LGBT equal rights demands can contribute, to some extent, to reinforcing heteronormativity. Implications concerning strategies for challenging the regime of normality and queering kinship are discussed.